2020
DOI: 10.1039/d0re00093k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-trifluoromethylated 1,3-butadienes via a Pd(0)-catalyzed fluorinated Heck reaction

Abstract: 1,3-Butadienes play a key role in modern synthetic chemistry and biochemistry because they are well-known precursors for the synthesis of retinoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In 2020, Li and co‐workers reported the palladium‐catalyzed Heck reaction of acrylamides 20 with BTP (Scheme 12). [19] The reaction worked smoothly without any metal additives under mild conditions. A variety of functional groups can be tolerated and a series of 3‐trifluoromethylated 1,3‐butadienes 21 could be obtained in good to excellent yields with high regioselectivity and s‐trans / s‐cis ratios.…”
Section: Cross‐coupling Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2020, Li and co‐workers reported the palladium‐catalyzed Heck reaction of acrylamides 20 with BTP (Scheme 12). [19] The reaction worked smoothly without any metal additives under mild conditions. A variety of functional groups can be tolerated and a series of 3‐trifluoromethylated 1,3‐butadienes 21 could be obtained in good to excellent yields with high regioselectivity and s‐trans / s‐cis ratios.…”
Section: Cross‐coupling Reactionsmentioning
confidence: 95%
“…[5][6][7][8] On the other hand, 3,3,3-trifluoropropynyl anion generated from BTP under the strong base conditions could also react with various electrophiles. [9][10][11] In the past decades, BTP has been widely used in classical cross-coupling reactions, either directly [12][13][14][15][16][17][18][19][20][21][22][23] or through conversion into the corresponding organometallic species (B, Zn, Sn, Si and Li). [24][25][26][27][28][29][30][31][32] Interestingly, the application of BTP as a coupling partner to the CÀ H bond functionalization would be of significant value for the synthesis of trifluoromethylated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, our research group also reported the synthesis of palladium‐catalyzed enamide‐directed 3‐trifluoromethylation of 1,3‐butadienes. [ 32 ] This type of compound can be synthesized by using cheap trifluoromethylation reagents. However, we believe that the reaction atom economy needs to be improved, and the synthesis of 4‐trifluoromethylated 1,3‐butadienes cannot be achieved using the method described in that report.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“… 16 Developing methods to efficiently convert the compound into fluorine-containing fine chemicals remains a very meaningful area for future research. To develop a simpler and more efficient method to synthesize α-CF 3 amides and as part of our continued interest in the area of trifluoromethylation 17 and carbonylation, 18 here, we envisaged a one-step sequential synthetic strategy that involved the direct carbonylation of anilines with an inexpensive and available trifluoromethylated olefin that could yield the desired α-CF 3 amides in a controlled manner ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%